East African giant millipedes of the tribe Pachybolini (Diplopoda, Spirobolida, Pachybolidae) - Enghoff, Henrik (Zootaxa, 2011)
The East African species of the millipede tribe Pachybolini are revised. Three new genera are described: Crurifarcimen n. gen. (monotypic, type species: C. vagans n. sp., Tanzania), Hyperbolus n. gen. (type species: H. apicomplexus n. sp., Tanzania and Uganda; further species: H. morogoroensis Kraus, 1958, Tanzania, transferred from Pachybolus), Parabolus n. gen. (type species: Trigoniulus dimorphus Carl, 1909, Tanzania, transferred from Pachybolus, further species: P. calceus n. sp., Kenya). Hadrobolus Cook, 1897 and its only species, H. crassicollis (Peters, 1855), Mozambique, are redescribed. Epibolus bravensis (Silvestri, 1897) and E. mossabicensis Lawrence, 1967, are both synonymised under E. pulchripes (Gerstäcker, 1873), Somalia to Mozambique, rendering Epibolus Cook, 1897, monotypic. Pachybolus Cook, 1897, is restricted to its poorly known type species, P. tectus Cook, 1897, Zanzibar. A cladistic analysis of Pachybolini (W Africa, E Africa, Madagascar) does not support monophyly of the East African genera, but does support a clade consisting of Crurifarcimen+Hyperbolus+Parabolus, as well as monophyly of the two latter genera.